IMPROVING TEACHER PERFORMANCE THROUGH JOB SATISFACTION AS A MEDIATOR OF SERVANT LEADERSHIP AND SELF-EFFICACY - Wendy Prawiro; Lianto; Sunardi Ginting (Management and Sustainable Development Journal, 2025)
This research seeks to examine and validate the influence of Servant Leadership and Self-Efficacy approaches on teacher performance within educational institutions, with perceived support for job satisfaction serving as a mediating variable. The quantitative approach was selected to fulfill the aforementioned research objectives. This study involved 116 teacher respondents from schools managed by the Yayasan Pendidikan Gembala Baik Pontianak. This associative study gathered primary data using questionnaires employing saturated sampling methods. The collected data were analyzed utilizing the method with WarpPLS 7.0. This study revealed that Servant Leadership and Self-Efficacy, mediated by job satisfaction, have a favorable and significant influence on performance. The research demonstrated that Servant Leadership and Self-Efficacy have a favorable and significant impact on job satisfaction, while Servant Leadership alone did not significantly affect performance. Managers of educational institutions are encouraged to implement Servant Leadership and Self-Efficacy to enhance job happiness, hence elevating teacher performance.